2010
DOI: 10.4161/cc.9.11.11840
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle re-entry mechanisms after DNA damage checkpoints: Giving it some gas to shut off the breaks!

Abstract: In order to maintain genetic integrity, cells are equipped with cell cycle checkpoints that detect DNA damage, orchestrate repair, and if necessary, eliminate severely damaged cells by inducing apoptotic cell death. The mitotic machinery is now emerging as an important determinant of the cellular responses to DNA damage where it functions as both the downstream target and the upstream regulator of the G2/M checkpoint. Cell cycle kinases and the DNA damage checkpoint kinases appear to reciprocally control each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Long-time-course experiments in which HeLa cells were treated with DOXO for 24 hr, followed by drug washout, revealed that the most dramatic Golgi dispersal persisted for at least 5 days (Figure S2A). Moreover, the Golgi remained detectably dispersed at least 30 days after the initial DNA damage occurred (Figure 2B), at a time when cell proliferation has completely recovered (van Vugt and Yaffe, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-time-course experiments in which HeLa cells were treated with DOXO for 24 hr, followed by drug washout, revealed that the most dramatic Golgi dispersal persisted for at least 5 days (Figure S2A). Moreover, the Golgi remained detectably dispersed at least 30 days after the initial DNA damage occurred (Figure 2B), at a time when cell proliferation has completely recovered (van Vugt and Yaffe, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…The response occurs quickly and is detectable within 4 hr after exposure to DNA-damaging agents, yet it also persists for weeks after transient exposure to DNA-damaging agents. This persistence could be due to the stability of a small number of DNA breaks that continue to activate the pathway (van Vugt and Yaffe, 2010) or it may indicate the existence of a positive feedback loop that maintains the Golgi dispersal once it is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…56 In certain model organisms, such as budding yeast and frog, after a prolonged arrest, cells can enter mitosis even with unrepaired DNA lesions. This process is called DNA damage adaptation, 57 and the DNA damage mediator Claspin has been shown to regulate the DNA damage adaptation process. 58 It is worth noting that Claspin also interacts with PLK1.…”
Section: Discussionmentioning
confidence: 99%
“…Because the kinase activity of CDK1/cyclin B1, Aurora A, and PLK1 are all downregulated by DNA damage (Fig. 4C), 4,57 they are less likely to be the contributing kinases. Therefore, checkpoint kinases such as ATR and Chk1 could be the potential candidates.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…These types of simulations can be used to help guide experimental investigation as well as verify that our understanding of the protein-protein interactions underlying the G2 to M transition and G2 arrest mechanism is correct. The model not only recapitulates the published behaviors of the G2 to M transition and DNA damage G2 checkpoint (Rieder, 2011; van Vugt and Yaffe, 2010; van Vugt et al, 2010) but also predicts a novel regulation of intracellular trafficking of MPF that requires pkMyt1.…”
Section: Introductionmentioning
confidence: 68%